Hierarchical Porous Batio3 Nano-Hexagons as A Visible Light Photocatalyst - Bantawal, Harsha; Krishna Bhat, D (International Journal of Engineering and Technology, 2018)
Hierarchical porous BaTiO3 nano-hexagons was synthesized via a simple hydrothermal route by using TiO2 and Ba(OH)2.8H2O as starting materials under alkaline environment and its photocatalytic activity was evaluated under visible light by taking methylene blue (MB) as a model pollutant. The prepared BaTiO3 was characterized by powder X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FESEM), energy dispersive X-rays analysis (EDX), high resolution transmission electron microscopy (HRTEM), Brunauer-Emmett-Teller (BET) analysis and diffused reflectance spectroscopy (DRS) techniques. It is noteworthy that the BaTiO3 nano-hexagons exhibited significant photocatalytic activity towards the degradation of MB under visible light irradiation. This significant photocatalytic activity of BaTiO3 under visible light is mainly attributed to the special morphology and formation of Ti3+ defects.Â Â